Food policy indicators: Tracking change: International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
This section provides updates on data generated by IFPRI research in 2016 and illustrations of key trends.